KAJIAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA PENGUKURAN KINERJA LINGKUNGAN PERUMAHAN VILLA ZEQITA MEDAN TUNTUNGAN DI MASA PANDEMI COVID-19 - Wati, Khalida (Sepren, 2024)
ABSTRACT This research calculates the selection of priorities that influence the measurement of environmental performance, namely using the Analytical Hierarchy Process (AHP) method, which is one of the decision making methods. To determine the priority level of choice, several dimensions can be used as a reference in measuring environmental performance. And in this research, 5 dimensions were obtained as a reference in determining priority levels in measuring environmental performance at the Villa Zeqita Medan Tuntungan housing complex during the Covid-19 pandemic, namely Accessibility, Drainage, Commercial Facilities, Waste Management and Green Open Space. The study carried out in this research was based on the results of a survey on the level of satisfaction of housing communities during the pandemic, which was then determined by ranking and arranging priorities using the AHP method. The results of the AHP analysis in this study concluded that the Accessibility criterion was the highest priority criterion for measuring residential environmental performance, with a weight of 0.359 or 35.9%. Then there are the Commercial Facilities criteria with a weight value of 0.251 or 25.1%, the Drainage criteria with a weight value of 0.203 or 20.3%, the Waste Management criteria with a weight value of 0.101 or 10.1% and finally the Green Open Space criteria which also have a weight value, namely 0.087 or 8.7%.